Utilization of Herbal Herbs for Health to Increase Body Immunity During the Covid-19 Pandemic In Kraksaan District, Probolinggo Regency, East Java Province - Dhany, Umi Rahma; Puji, Murtias; Aulia, Regina; Antika, Tri (IMPOWERMENT SOCIETY, 2022)
In the midst of a pandemic crisis like this that has not yet subsided, the government has carried out medical treatment in various regions. Not only that, medical treatment is deemed insufficient to ward off the covid 19 virus. Therefore, traditional treatment is needed as an alternative that can be used in the community to increase body immunity in order to break the chain of transmission of covid 19 that occurs in Indonesian society. Therefore, people entrust traditional herbal medicine as an ingredient to increase body immunity during a pandemic like the current one, which is to ward off various diseases, especially the current troubling conditions. So the purpose of writing this community service program is to optimize herbal medicine as the use of herbal drinks in increasing body immunity. In the process of making herbal medicine, it cannot be separated from the cultivation of family medicinal plants or toga such as turmeric, temulawak, ginger, basil, lime and tamarind. This outreach and counseling is targeted at the general public, especially in the Kraksaan, Probolinggo, where understanding and knowledge related to herbal medicine is more realized from disseminating video tutorials for making herbal medicine, which is expected to be used by the community in their respective homes to prevent transmission covid 19 virus.